The Impact of Teaching Medical Devices Course Using Active Learning Strategies in The Academic Achievement of The Fourth Year Biomedical Engineering Students at The University of Science and Technology, Republic of Yemen - Fadhl Alakwaa; Mahmoud Alroumamah; Zyad Algaboby (University of Science and Technology, Yemen, 2016)
Abstract: The aim of the current research is to explore the impact using active learning strategies in the teaching of medical devices course in the achievement of fourth year biomedical engineering students compared to the conventional teaching method. To achieve this aim, authors have stated the following statistical hypothesis: There is a statistically significant difference (at the 0.05 level) between the mean scores of students of the experimental group (taught using active learning) and control group students (taught in the usual way) in the post application of the test grades at each of the following levels: remembering, understanding, application, analysis. Experimental design known as pre and post measuring design is used in this research. Research sample consisted of two groups of the fourth level engineering biomedical students.    First group (control group) and second group (experimental group) consist of 20 students. To measure the performance of pre and post in the experimental and control groups in academic achievement, researchers developed a test to measure achievement in objective (a pump fluid, and a defibrillator) at levels: remembering, understanding, application, analysis was confirmed the veracity of the tool are viewing on a group of arbitrators, as it was ascertained where the validity test reliability coefficient (0.72). After we get results from pre and post-test, data were manipulated and processed using t test to validate research hypothesis. Pre-research tool is applied on the control and experimental groups. Then two selected subjects (Infusion pump and defibrillator) were taught for the two groups using two different methods. Experimental group was taught using active learning strategies whereas control group was taught using conventional method. After teaching period (4 classes) for every group, we applied research tool on the two groups.  Results show statistically significance difference (at 0.01) between control and experimental average scores at post-test in the following levels: Remembering, understanding, implementation and analyzing. Authors recommended encouraging teachers using active teaching strategies in teaching students to increase student's scientific achievements.